Analisis Tingkat Keterampilan Passing dan Dribbling Siswa Pada Ekstrakurikuler Futsal di SMA N 1 Kepahiang - Gunatama, Fahmi Ilham; Syaputra, R.; Martiani, Martiani; Sumantri, Ajis (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the analysis of the level of passing and dribbling skills of students in extracurricular Futsal at SMA N 1 Kepahiang. This research uses quantitative descriptive research, with the type of survey method. The sample in this study amounted to 20 futsal extracurricular participants at SMAN 1 Kepahiang.The data collection techniques in this study used tests and measurements. Based on the results of the research that has been carried out, it can be concluded that the analysis of the level of passing and dribbling skills of students in extracurricular Futsal at SMA N 1 Kepahiang, based on the basic skills test of playing futsal, it is known that the excellent category is 5 participants, the good category is 11 participants, the moderate category is 3 participants, the deficient category is 1 participant, and the category is very poor 0 participants.